PENGARUH STRATEGI THINK TALK WRITE TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SEKOLAH DASAR - Maydasari, Maydasari; Margiati, Margiati; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the influence of the use of think talk write strategy to the results of learning mathematics class IV State Elementary School 9 Sungai Kakap. The research method used is experimental method. The research form is pre-experimental design with one group pretest-posttest research design. The population is all the fourth graders of State Elementary School 9 Sungai Kakap consisting of 80 students and the sample of students of grade IV C State Elementary School 9 Sungai Kakap consisting of 26 students. Based on data analysis, that the average results. Based on the data analysis obtained the average result of pre-test of students 57,5 and average result of student's post-test 70,5. The result of t test is obtained tcount 3.13 while ttable with db = 26-1 = 25 and significant level (α) = 5% is 1.706, it turns thitung ≥ ttable or 3.13 ≥ 1.706 Ha is accepted which means there is influence of using strategy think talk write to student learning outcomes in learning mathematics class IV. From result of calculation effect size (ES), obtained (ES) equal to 0,73 with criteria classified moderate. This means that the use of the think talk write strategy has a moderate effect on the learning outcomes of the fourth grade mathematics learning at the Kuhap State Elementary School 9 Sungai Kakap. Keywords: Influence, Think Talk Write Strategy, Learning Outcomes, Mathematics